Sulfuric acid speleogenesis in Greece - Lazaridis, Georgios Theodoros; Melfos, Vasilios; Papadopoulou, Lambrini; Onac, Bogdan P.; Stergiou, Christos L.; Maravelis, Angelos G.; Voudouris, Panagiotis; Dora, Despoina; Fitros, Michalis; Papaioannou, Haritakis; Vouvalidis, Konstantinos (Acta Carsologica, 2024)
Manifestations of sulfuric acid speleogenesis (SAS) documented in several caves in the areas of Aghia Paraskevi, Konitsa, W. Peloponnese, Elassona, Lavrion and Kammena Vourla in Greece are examined and discussed in this work. Carbonate and sulfate samples collected from caves in Aghia Paraskevi and western Peloponnese areas were investigated using methods, such as fluid inclusion, scanning electron microscopy, carbon, sulfur and oxygen stable isotopes, X-ray powder diffraction, and chemical analysis. The examined caves are mainly developed at or in the proximity of the local water table and they are related to hydrothermal springs and geothermal fields. In addition to the documentation of SAS in one case study from Aghia Paraskevi, calcite spar with a homogenization temperature peak at 280°C, indicates an early speleogenetic stage that involves meteoric-origin hydrothermal fluids under deep-seated settings. Sulfur isotope composition of sulfates (–4 ‰) is indicative for pyrite oxidation. The Konitsa caves represent a system developed at multiple altitudes that is related to the evolution of Sarantaporos River. The caves in West Peloponnese are located in two different geotectonic units. However, the caves in both units are active and share common characteristics, such as their development near sea level, morphology and fracture-guided pattern, and the presence of gypsum with δ34S values (average –26 ‰) that are plausibly related to hydrocarbons and bacterial activity. Morphological and geochemical aspects of the caves in these two regions suggest long-lasting, multiphase speleogenetic systems.